Raising awareness of conflict of interest in performing public service of cadres, civil servants, and public employees - Nguyen Thi Ngoc Lan (Journal of State Management, 2024)
Conflict of interest represents an objective situation tied to the public service activities of cadres, civil servants, and public employees. If not fully recognized, it can negatively affect the quality and efficiency of public service execution and undermine public trust in the leadership of the Party and the State’s governance, compromise transparency and objectivity in public service. Unchecked conflicts of interest potentially lead to embezzlement, corruption, harmful practices, and group interests. These risks contribute to moral decline, ethical degradation, and the alienation of officials, civil servants, and public employees, threatening the Party’s sustainability. Therefore, raising awareness among officials, civil servants, and public employees about conflicts of interest in public service execution is a critical and objective task. It plays a significant role in promoting Party building and strengthening efforts.